Hygienic Milk Production, Milk Marketing And Milk Quality Evaluation in Urban and Peri-Urban of Sululta District, Ethiopia. - Gutema, Ararsa (Discoveries in Agriculture and Food Sciences, 2022)
The study was conducted in Sululta district, Oromia special Zone Surrounding Finfinnee, with the objective of assessing hygienic milk production, marketing system and milk quality evaluation. Raw milk marketing channels producers to Collectors (80%), producers to processors (19%) and producers to consumers (1%), with the average milk price (25) Ethiopia Birr/L during the study was conducted. The overall mean of fat 2.968±0.27%, protein 2.71±0.149%, specific gravity 1.0161±0.0007, Sold-non-fat 5.91±.396, temperature 23.8±.97℃, added water 23.11± 5.049%, freezing points -0.4027±0.0364℃, titratable acidity 0.151±0.009 and pH 6.293±0.077 and there was significant (P≤0.05) difference while milk temperature was not significant (P≤0.05) difference between the two study areas. The overall mean of total bacterial count 7.80±0.25log10cfu/ml, Coliforms 5.71±0.24 log10cfu/ml, Somatic cell 1.10±0.414 log10cfu/ml and yeast and mold 4.13±0.168 log10cfu/ml, there was significant (P≤0.05) difference milk microbial quality between the two study areas. High bacterial load of milk due to contamination from fecal or other contaminating agents from poor pre-harvesting and post harvesting of milk handling, insufficient udder preparation, use of poor quality and un-boiled water for cleaning utensil. The chemical composition and microbial quality of milk not fulfilling milk quality standards, except titratable acidity and somatic cell count, might be due to milk adulteration, cream separation and neglected hygienic milk production practices etc. Appropriate intervention of concerned technical supportive stakeholders would be essential to overcome prevailing poor hygienic milk production, milk marketing and milk quality problem in general.